Wound Infection in Gynecologic Surgery. Issue 5 (2000) - Kamat, Aparna A.; Brancazio, Leo; Gibson, Mark
Abstract : Objective: We sought to determine the wound infection rate among patients undergoing elective gynecologic surgery at a single tertiary care center and to determine the predictive value of various factors that contribute to infection. We further investigated the adequacy of hospital records in documenting infection rates as well as the timing of presentation of wound infections. Methods: The records of 115 patients undergoing elective gynecologic surgery at our institution were reviewed. Patients were further subdivided based on route of surgery. We analyzed the importance of antibiotic prophylaxis, route of surgery, smoking, diabetes, and body mass index (BMI). Results: The overall wound infection rate was 12.17% with no significant difference in the subgroups by route of surgery. Overall, antibiotic prophylaxis significantly decreased infection rates ( P = 0.0118), but the route of surgery, BMI, smoking, and diabetes were not significant predictors of infection. Only one case of infection was detected during the initial hospital stay (6.1%). Fifty percent of the patients with infection required readmission, and of these 35.7% required an additional surgical procedure. The average length of hospital stay was 2.4 days longer in patients with infection. Conclusions: Antibiotic prophylaxis has a role in the management of patients undergoing abdominal gynecologic surgery. In today's environment of cost containment, an increased hospital stay and the added likelihood of additional surgical intervention associated with wound infection are important targets for prevention. Most patients with wound infection were diagnosed after discharge from the hospital. In our population, among whom transportation problems and remote residence are prevalent, strategies for infection surveillance should be integral to discharge planning. Infect. Dis. Obstet. Gynecol. 8:230–234, 2000.